Lupus nephritis association with idiopathic CD4 + T lymphocytopenia: a case report of a young man with recalcitrant warts - Tingting Wang; Shaojun Liu; Xiaowan Liang; Jun Xue; Li You; Xiaoye Zhu (BMC Nephrology)
Abstract Introduction Systemic lupus erythematosus (SLE) is an autoimmune disease in which the immune system is in a disordered state, with excessive production of autoantibodies and abnormal functions of immune cells. This imbalance in the immune system alters the body’s defense capabilities against various pathogens. Patients with idiopathic CD4⁺ T lymphocytopenia (ICL) have a reduced number of lymphocytes, and the function of the immune system is also impaired. Human papillomavirus (HPV) infects human body and mainly lurks and replicates in skin and mucosal cells. Case report A 35-year-old Chinese male was admitted to the Nephrology department, with a three-year history of recalcitrant warts and a six-month history of generalized edema and fatigue. Physical examination identified verruca vulgaris on the limbs and face. Laboratory examinations demonstrated CD4⁺ T lymphocytopenia, low levels of C3 complement, and positive antinuclear antibodies. Renal function tests indicated nephrotic syndrome. Renal biopsy findings were consistent with Class V lupus nephritis (LN). Based on the 2019 EULAR/ACR criteria, the patient was diagnosed with systemic lupus erythematosus (SLE) and treated with prednisone and tacrolimus. However, after six months, no remission was observed. With the administration of Belimumab, a significant improvement in his renal symptoms and stabilization of cutaneous lesions were noted at the 12-month follow-up. Conclusion This particular case emphasizes the significance of taking into account the potential presence of underlying immunodeficiency in patients with recalcitrant warts and formulating appropriate treatment strategies. Such patients necessitate meticulous and continuous follow-up by both the dermatology and immunology specialties to vigilantly monitor the emergence of other diseases associated with ICL. Belimumab has manifested outstanding efficacy and safety profiles in SLE patients with compromised immune function.